Jovens na Educação de Jovens e Adultos: Produção do fracasso no processo de Escolarização - Furtado, Quezia Vila Flor (2008)
Youth has been recognized as a crescent and expressive age group at Youth and Adult Education (YAE), which has found in this modality a distinguished space for its real needs, having for main challenges: the situation of scholar failure and reduced reflection towards pedagogic-didactic strategies capable of attending to its interests and expectations. For that purpose, our objective with this paper is to identify and analyze the main factors that have contributed for a permanent presence of youth at YAE of primary classes. This research follows a qualitative approach, which offer us, in analysis and description, larger proximity to the object of study. We worked with participating observation, carried out from July to December of 2007 in five (05) classrooms, placed in three (03) municipal schools of João Pessoa PB, and with the semi-structured interview done with ten (10) student youngsters and (09) student adults from Cycle I and II of the same schools. For theoretical reference we took the literature about youth and scholar failure. For youth, we approached the different conceptions that involve this category with Abramo and Leon, and specifically to the youth from YAE with Carrani, Peregrino and Ribeiro. For scholar failure we approached the studies of Charlot, followed by Freire, Aquino, Frei Beto, Gentili, Sousa Santos, among others. The analysis of the gathered material points situations of failure lived by the youngsters while still children, referring to deficiencies related to knowledge, plus finding similar situations when arriving at YAE . This reality reveals the production of scholar failure in some institutions of public education, with the permanence of a degraded education process that, in childhood or youth, offers little opportunities of overcoming this social situation, lived by many people that come from popular groups.